Preparation and Surface-Modification of Alumina/Silica Composite Nanoparticles - Jiao, Da; Zheng, Shaohua; Xu, Hongyan; Cao, Bingqiang (Asian Journal of Chemistry, 2011)
In this work, alumina/silica (Al2O3/SiO2) composite nanoparticles were prepared using aluminum isopropoxide and tetraethyl orthosilicate as raw materials. We prepared Al2O3 and SiO2 precursors with sol-gel method and Al2O3/SiO2composite nanoparticles by hydrothermal method, respectively. We in situ modified Al2O3/SiO2composite nanoparticles and optimized the modifier and modification route. The characterizations of the Al2O3/SiO2composite nanoparticles were performed with transmission electron microscopy, X-ray diffraction, infrared spectroscopy and Zeta potential analysis. Under the optimized modification conditions, the modified Al2O3/SiO2composite nanoparticles had good dispersion and suspension. The surface of the Al2O3/SiO2composite nanoparticles was changed from hydrophile into lipophilicity.